Komunikasi Guru-Siswa di Indonesia dalam Perspektif Guru dan Siswa Sekolah Menengah Pertama (SMP) - Justin, Ernest; Widiyanto, Yohanes Baptista Cahya; Kristiyani, Titik (Fakultas Psikologi Universitas Sanata Dharma, 2023)
Communication in education, especially that occurs between teachers and students, has been shown to have an impact on many educational outcomes, both individual and communal. Communication relates to the cultural context, based on some literatures about teacher-student communication, there are also variations according to the cultural context in which communication occurs. For this reason, this study aims to find out how the concept of teacher-student communication is in Indonesian school context. This type of research is qualitative. Participants in the study were teachers and students at the junior high school (SMP) level. The data collection method was a survey using an open questionnaire. Data analysis used thematic content analysis. The results show that direct and indirect (online) communication has different dynamics. Students tend to feel more comfortable when communicating directly.